2015
DOI: 10.1039/c5ob00460h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new carolacton derivatives and their activity against biofilms of oral bacteria

Abstract: Carolacton, a secondary metabolite isolated from the extracts of Sorangium cellulosum, causes membrane damage and cell death in biofilms of the caries-and endocarditis-associated bacterium Streptococcus mutans. Here, we report the total synthesis of several derivatives of carolacton. All new structural modifications introduced abolished its biological activity, including subtle ones, such as inversion of configuration at C9. However, a bicyclic bislactone derivative as well as the methyl ester of carolacton re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 33 publications
3
47
0
Order By: Relevance
“…289 Given that each of these could be hydrolyzed to yield carolacton, it was hypothesized that these derivatives were merely acting as pro-drugs. Kirschning and co-workers did indeed detect small quantities of carolacton in the supernatant, indicating a weak pro-drug effect.…”
Section: Narrow-spectrum Small Molecule Natural Productsmentioning
confidence: 99%
“…289 Given that each of these could be hydrolyzed to yield carolacton, it was hypothesized that these derivatives were merely acting as pro-drugs. Kirschning and co-workers did indeed detect small quantities of carolacton in the supernatant, indicating a weak pro-drug effect.…”
Section: Narrow-spectrum Small Molecule Natural Productsmentioning
confidence: 99%
“…9 Kirschning in particular has been quite prolific as they have disclosed both the first total synthesis 10 and uncovered useful information regarding the structure—activity relationship (SAR) by analog synthesis (Figure 1). 11 These studies elucidated that both drastic (increased ring size) and even small conformational changes to the 12-membered macrocycle, for example, introduction of an α,β -unsaturated ketone or an epimeric allylic alcohol, abolish activity. Further, the side chain ketone was thought to be essential and “pro-drug” ester derivatives affected biofilm development at concentrations relative to their rate of hydrolysis indicating that carolacton, and not the analogs, were responsible for activity.…”
mentioning
confidence: 99%
“…Of note, these analogs contain a carboxylic acid that appears to be important for bioactivity as the corresponding alcohols are inactive (Figure S1), consistent with the findings of Kirschning. 11 …”
mentioning
confidence: 99%
“…Interestingly, the methyl ester variant ( 127 ) and bis‐macrolactone ( 129 ) analogs displayed activity comparable to carolacton itself. It was shown that these compounds act as pro‐drugs, being hydrolyzed in vivo by S. mutans hydrolase enzymes to generate carolacton, thereby restoring bioactivity . Taken together, these findings demonstrate the highly specific interaction of carolacton with its biological target and provide valuable information to guide future analog development.…”
Section: Other Examples Of 12‐membered Macrolactonesmentioning
confidence: 80%
“…The Kirschning group has also reported the synthesis of several carolacton analogs, providing useful SAR information (Figure ). The methyl ester derivatives 127 and 128 were obtained by modification of carolacton itself.…”
Section: Other Examples Of 12‐membered Macrolactonesmentioning
confidence: 99%